Internet health information seeking by primary care patients - Noemí Terrero Ledesma; Alberto Nájera; Ricardo Enrique Reolid-Martínez; Francisco Escobar-Rabadán (Rural and Remote Health, 2022)
Introduction: As patients seek health information more frequently on the internet, the impact on their health status and their relationship with doctors could be a matter of concern. The objective of this study is to know how frequently rural primary care patients seek health information on the internet and the factors associated with it. Methods: This cross-sectional study surveyed 850 patients aged over 15 years who attended two rural health centers in Cuenca (Spain). Consecutive case sampling was done. The participants were invited to answer a survey with sociodemographic and clinical aspects, and questions about possible internet searches for health information. The statistical analysis included the description of the variables and a bivariate analysis, and was completed with a logistic regression analysis. Results: Patients' median age was 54 years, interquartile range 39-67 years; 60.9% were female. Of those surveyed, 49.8% (95% confidence interval 46.3-53.2) stated that they used the internet to seek health information. Statistically significant differences were apparent for gender, age, level of education, disease and attendance (p<0.0001). A logistic regression analysis showed an independent relationship with health information seeking on the internet for the variables gender, age, level of education (p<0.0001) and having a chronic disease (p=0.004). Conclusion: Roughly half the primary care patients in the rural area sought health information on the internet. Females, young people, those with a higher level of education and a chronic disease background did so more frequently.